The effect of river regulation on groundwater flow patterns and the hydrological conditions of an aapa mire in northern Finland - Åberg, Susanne; Korkka-Niemi, Kirsti; Rautio, Anne Brita Kristina; Åberg, Annika (Journal of Hydrology: Regional Studies, 2022)
Study region Northern Finland. Study focus This study examined long-term (decade-scale) hydrological and ecological consequences of dam construction and subsequent river regulation on the environmentally protected Viiankiaapa mire. Pre-regulation floods affected the hydrology of the riverbanks and the Viiankiaapa mire, which contain habitats of flood-dependent or groundwater-influenced ecosystems. Groundwater discharge and flow patterns and pre-regulation flood coverage were simulated to investigate the impact of river regulation on the mire area. New hydrological insights for the region The flood models indicate that regular flooding covered the westernmost part of the mire before the regulation. Groundwater modelling suggests that the regulation has raised the locations of springs in the river shore, reduced the hydraulic gradient towards the river, raised the groundwater table in the river banks and the western part of the Viiankiaapa mire, and increased groundwater discharge in the mire. The groundwater flow models and the stable isotopic composition of water indicate that the constructed dam changed the groundwater flow directions close to dam. The ecological effects of regulation were mixed: the studied flood-dependent plant species declined due to the reduction in floods after regulation. Conversely, the occurrence of Hamatocaulis vernicosus and Hamatocaulis lapponicus appears to be related to the high water table and groundwater discharge areas in the mire, suggesting suitable habitat for these species may have expanded after the regulation. Peer reviewed